Knowledge and attitude towards dried blood spot (DBS) of HIV exposed infant of mothers attending postnantal and under five clinics in Kabwe district of Zambia - Kangwa, Charles Chanda; Kapansa, Chibale; Swema, Manson Manda (Lusaka: University of Zambia , School of Medicine, 2016)
The global targets of getting zero deaths from AIDS-related illness can only be met if all HIV infected infants can be diagnosed through NDA PCR and initiated on Highly Active Antiretroviral Therapy (HAART) as early as four to six weeks of age. The aim of this study was to assess knowledge levels and attitude towards DBS of HIV exposed infant of mothers attending postnatal and under five clinics in order to make strategic recommendatons to the health authorities on how to scale up the services in the various health facilities.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Polymerase Chain Reaction--methods.; Virus Diseases--drug therapy--Child.; Virus Diseases--diagnosis; Infection in children